Sosialisasi Budaya Tertib dan Etika dalam Menggunakan MRT bagi Para Santri di Pondok Pesantren As-Sa’Adah, Garut - Yana Tatiana; Dian Artanti Arubusman; Aceng Taopik Gumelar (Institut Transportasi dan Logistik Trisakti, 2022)
An orderly and ethical culture is important in using Mass Transportation Modes.The existence of the MRT also creates a culture of order and ethics in transportation. The number of Indonesian people who do not know the culture of ethics and order in transportation, especially among the younger generation, is an important thing that must be considered. The students at the As Sa-adah Islamic Boarding School located in Garut also have an interest in using the MRT. A relatively new and modern mode of transportation. The socialization carried out to the students of the As-Sa-adah Islamic Boarding School showed a change in their understanding of the importance of ethical culture. and orderly in using transportation modes, especially MRT